Transformasi Produk Sekunder Pengolahan Minyak Parede Sebagai Produk Sambel Kerak Minyak - M. Yasser; Andi Nurul Istiyana; Andi Muhamad Iqbal Akbar Asfar; Andi Muhammad Irfan Taufan Asfar; Ady Kurnia (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Coconut oil processing or what is known by the Bugis people in South Sulawesi, namely Parede Oil, leaves a secondary product in the form of oil crust. This oil crust is not fully utilized, especially as a product that can increase its selling value. Therefore, this community service in the form of a community partnership program conducts training in processing oil crust into oil crust sauce. Until now, this product has survived with a shelf life of more than 4 months without the addition of any preservatives. This product is packaged in a chili pot with a net weight of 60 grams. This program has succeeded in improving the skills of partners, namely the PKK Latellang Village, Patimpeng District, Bone Regency, South Sulawesi Province, in utilizing oil crust to become oil-based chili sauce which has high economic value.